EFEKTIVITAS REKONSTRUKSI ASESMEN NUMERASI BERBASIS STEAM DALAM PENDIDIKAN VOKASI DI SMK WERDHI SILA KUMARA - I Made Darmada; Ni Made Pira Erawati (Widyadari, 2026)
This study aims to analyze the implementation and effectiveness of a reconstructed STEAM-based numeracy assessment model in improving vocational students’ competencies at SMK Werdhi Sila Kumara, as well as to examine its impact on students’ competency development. The study employed a mixed methods approach with an exploratory sequential design, integrating qualitative and quantitative methods in a systematic manner. The research stages included needs analysis, model design, expert validation, limited testing, field testing, and model finalization. The results indicate that the developed STEAM-based numeracy assessment model demonstrates high validity and reliability, making it suitable for use in vocational learning contexts. The implementation of the model received positive responses from both teachers and students and was found to support more contextual, applied, and student-centered learning processes. Furthermore, quantitative findings reveal an improvement in students’ numeracy competencies following the implementation of the STEAM-based assessment model. These findings suggest that STEAM-based numeracy assessment is effective in enhancing student engagement, critical thinking skills, and contextual problem-solving abilities. Therefore, the developed assessment model has the potential to serve as an innovative alternative in advancing vocational education assessment systems that are aligned with workforce demands and 21st-century skills.